LEVERAGING SALESFORCE FOR DIGITAL GOVERNMENT TRANSFORMATION - Anirudh Sharma Peri (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive technical article explores the transformative impact of Salesforce's Government Cloud platform on public sector operations and service delivery. The article examines how cloud-based solutions are revolutionizing government agencies worldwide, focusing on key areas including security frameworks, operational excellence, crisis management capabilities, and data-driven decision-making. The article investigates the platform's architecture, technical components, and integration capabilities, highlighting its role in enhancing citizen services, improving operational efficiency, and enabling digital transformation. Through detailed analysis of implementation cases and performance metrics, the article demonstrates how the platform addresses critical challenges in government operations while maintaining stringent security standards and compliance requirements.